ANALYSIS OF THE EFFECTIVENESS OF METAL COVER IN PREVENTING RADIATION LEAKAGE IN MICROWAVE-BASED GASIFICATION REACTOR - Rahayu, Vira; Ratnasari, Tri; Rahmatullah, Muhammad Arif; Pramono, Yono Hadi; Yudoyono, Gatut (Inovasi Fisika Indonesia, 2025)
Abstract Microwave-assisted gasification, which converts biomass and plastic waste into syngas, has significant promise for the production of clean renewable energy. This technology has the potential to reduce reliance on fossil fuels and address waste management challenges. Operational safety, particularly with microwave leakage, is a significant issue due to stringent standards for microwave exposure. This study evaluates the effectiveness of several metallic materials as microwave shields in microwave gasification reactors. This study investigates the effectiveness of 2 mm thick metal sheets made of copper, aluminum, iron, and stainless steel in reducing microwave leakage at a frequency of 2.45 GHz. Experimental results indicated that copper and aluminum are particularly effective shields. Copper attained a remarkable leakage reduction of 99.53% (from 105.6 W/m2  to 0.5  W/m2) while aluminum reached a decrease of 97.35% (from 105.6 W/m2 to 2.8 W/m2). Efficient reflection and absorption of microwave energy are facilitated by the extremely low skin depth values of both materials, which is consistent with their high effectiveness. However, iron and stainless steel also demonstrated a strong capacity to reduce leakage, with an efficacy of 89.96% (reducing leakage to 10.6 W/m2 ) and 73.86% (reducing leakage to 27.6 W/m2). Still, their performance was influenced by more complex magnetic properties. These results indicate that copper and aluminum are ideal choices for primary microwave shielding applications in gasification reactors. Conversely, iron and stainless steel, while less efficient as primary shields, offer excellent mechanical strength and corrosion resistance, making them suitable for auxiliary structural components. Therefore, a hybrid design integrating a thin shielding layer of copper or aluminum onto these structural elements is proposed for optimal microwave containment. This study provides crucial insights for the design of safer and more efficient microwave gasification reactors, thereby supporting the development of responsible renewable energy technologies.